EXPLORING GENDER ROLES IN THE STORY OF I LA GALIGO - Murni Mahmud (Sosiohumaniora, 2014)
This paper aims at exploring the gender roles in the story of I La Galigo. This story is an epic of the Bugissociety featuring the adventure and the lives of the first humans occupying and living in the Earth. Based on theanalysis, gender roles can be seen in the story, such as the roles of Datu Palinge’ as the wife who can influence thedecision making of the King, Sang Patoto’e. The reflection of gender can also be seen in the expected behaviorsof Bugis men and women for masculinity and femininity. Men are expected to be warani (brave) and women areexpected to be malebbi’ (modest). These expected behaviors can be seen from women characters, We Nyili’ Timoand We Datu Sengngeng, and from men characters, Batara Lattu’ and Sawerigading. Another gender issue can alsobe seen in the pattern of patrilineal society and the tendency to marginalize women’s position.Key words: Bugis society, I La Galigo, Gender roles.